Analysis of conditions sensitive to primary care in a successful experience of primary healthcare expansion in Brazil, 1998–2015. (September 2018) - Pimenta, L.; Dutra, V.G.P.; de Castro, A.L.B.; Guimarães, R.M.
Abstract: Objective: To analyze trends in expansion of coverage of the family health strategy and hospitalization for conditions sensitive to primary care (CSPC) in a successful experience of primary healthcare expansion in Brazil. Study design: Ecological study with data from the Brazilian National Health Information System. Methods: CSPC were analyzed between 1998 and 2015 in Rio de Janeiro, Brazil, by cause groups. Trends, variation, and correlation between indicators in the period were evaluated. Results: Most of the cause groups showed a reduction in hospitalization rate, particularly cardiovascular diseases and asthma, but an increase was seen for obstetric causes. The main causes of hospitalization were heart failure, cerebrovascular diseases, and bacterial pneumonia. The contribution of vaccine-preventable diseases, cardiovascular diseases, diabetes, nutritional deficiencies, and chronic lung diseases to the total number of hospitalizations was seen to decrease. Conclusions: Analysis demonstrates that the family health strategy, as access to the healthcare system, decreases the majority of CSPC hospitalization rates. Highlights: Rio de Janeiro experienced an expanding coverage of the family health strategy in a short period. This is an unexplored case in terms of coverage versus quality of care. Most of the group conditions present a decreasing trend to reduce hospitalization rate. Primary health care in Rio de Janeiro has a negative association to hospitalization rates.